KARAKTERISTIK DAN POLA PERGERAKAN PENDUDUK KOTA BATAM DAN HUBUNGANNYA DENGAN PERKEMBANGAN WILAYAH HINTERLAND - Imam Setyohadi (JURNAL DIMENSI, 2015)
Batam Island’s role as an industrial development center causes fast-paced growth in many sectors with an uneven inhabitant distribution. With most people inhabit the Batam city.The hinterland area is characterised by islands and housing pattern of community clusters in the form of fishermen’s neighborhood along the coastal region with most of the houses are semi-permanent buildings. Most of people’s activities there are consisted of fishing. With limited infrastructure, the mode of transportation used in between the many islands there is with motor boats (Pancung). This is very much in contrast with the condition down the Batam City, in terms of its socio-economic, housing and other aspects.This research is aimed at figuring out the reason as to why people prefer to have their house located in rural areas and finding out the characteristic pattern of people’s movement around the Batam Island.Samples were taken using the sample random proporsional method. Samples were taken randomly from many districts with a proper ratio of people from weak, middle and upper class economic strata. The data were then analyized with cross classification.Results show that people chose rural areas because that where the industrial locations are so that it is closer for them to go to work, and the housin price or rent there are relatively cheaper too. Whereas people who chose to live in the Batam City do so because they want to improve their livelyhood by opening up alternative businesses other than working within the industry.People’s traveling destination is in and around the rural areas because it is where the industries are located evenly and the rest of them travel to the areas surrounding Batam Island. Such as people of Nongsa, 23% of the travel to the Kabil industrial area, and 12% of them go to the city center (Nagoya). In contrast, people of the Sekupang District, 29% of them travel only in and around Sekupang area. Other than that only 2% of Batam inhabitants travel to the islands surrounding Batam Island. Whereas for the people of Sei Beduk, 29% of them go to Muka Kuning and 14% of them to the city center. And for the people of Lubuk Baja District, 32% of them go to the city center (Nagoya), because it is actually the CBD center.The type of transportation used by people in rural areas are mostly private vehicles because they are thought to be more comfortable and safe, as is the case for Nongsa and Sekupang. Nonetheless, 2% of Sekupang inhabitants use motor boats to travel to the islands surrounding Batam Island. In Nongsa, 36% of the people use motorcycle, public transportation account for 32%, and in Sekupang car owners are around 35%. Contrary, the people of Sei Beduk are mostly using public transportation, 42%, due to the already availabel public road and vehicles and only 34% use cars.As for the distance covered by those people, Nongsa and Sekupang residents are 42% cover around 5-10 Km with a travel time of 20-30 minutes a day. Whereas the people of Sei Beduk, 45% of them only cover 105 km in around 10 minutes a day due to the proximity of their living place with the industrial location.On the other hand, Lubuk Baja (city center) people are 43% using cars,  for the are much more comfortable and allow them to have higher mobility. And only 31% of the inhabitants there use public transportation. Most of the people there cover 1-5 km (52%) to 5-10 km (27%) a day with a travel time of around 10 to 20-30 minutes.